Survival rates and mortality risk factors in chronic hemodialysis patients in Chumphon Province, Thailand; a multicenter survival analysis study - Watcharananan, Yingluk; Indranoi, Artit (Journal of Medical and Public Health Region 4, 2026)
The incidence of end-stage chronic kidney disease (ESKD) in Chumphon Province has been steadily increasing, leading to a rise in the number of patients undergoing renal replacement therapy, particularly hemodialysis. This research aims to investigate the survival rate of ESKD patients undergoing hemodialysis in Chumphon Province. The study employed a retrospective cohort design, involving new ESKD patients who underwent hemodialysis from October 1, 2018, to December 31, 2022. A total of 154 patients were included in the study, and their survival status was monitored until December 31, 2024. The survival rate was analyzed using the Kaplan-Meier method, with statistical testing performed by the log-rank test, and risk factors assessed using Cox regression. The results revealed that, during the study period, 51 patients (33.12%) had died in the cohort. The mortality rate was 12 deaths per 100 patient-years (95% CI 9-15.59). The median survival time was 5.4 years. The survival rates after hemodialysis at 1 year, 3 years, and 5 years were 89%, 73%, and 53%, respectively. Factors independently associated with mortality after multivariable adjustment, included 8 factors: age greater than or equal to sixty years old, weight greater than 60 kg, comorbidities such as diabetes mellitus and cardiovascular disease, the use of a central venous catheter for dialysis, cholesterol levels greater than 200 mg/dL, albumin levels less than 3.5 g/dL, and a dialysis adequacy (Kt/V) less than 1.2